Optimalisasi Unit Proses Pengolahan Air Minum Pada Perusahaan Umum Daerah - M Alif Rifky; Wilma Nurrul Adzillah; Okti Dinasakti Nurul Mentari (Jurnal Serambi Engineering, 2024)
The International Research Centre (IRC) is one of the units in the IPA Poncol branch, which includes coagulation, flocculation, sedimentation, filtration and disinfection units with a capacity of 40 L/sec concrete building. Based on direct observation, the problem in the IRC unit is that the produced effluent is less than optimal, which is 29.4 l/sec, while the designed capacity of the IRC unit is 40 l/sec and does not match the existing process units in the IRC with the applicable design criteria. The cause of the sub-optimal discharge is due to a malfunctioning penstock in the flocculation unit, filter media that has not been replaced for a long time and some valves that have not been maintained. The design criteria that are not met by the IRC unit are the velocity gradient parameter multiplied by the retention time in the coagulation unit, the retention time in the flocculation and sedimentation unit and the backwash time in the filtration unit. The purpose of this study is to provide recommendations for the optimisation of the IRC process unit at Poncol Branch IPA. The method used is to analyse the existing conditions with applicable design criteria. The results of this study are to provide recommendations for the coagulation unit, namely the height of the inlet well to the coagulation basin, changes in the water level in compartment one of the flocculation unit, and changes in the volume of the sedimentation and filtration units.